2020
DOI: 10.3389/fmicb.2020.575031
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chromosomal Mutations Responsible for Fosfomycin Resistance in Escherichia coli

Abstract: Fosfomycin resistance in Escherichia coli results from chromosomal mutations or acquisition of plasmid-mediated genes. Because these mechanisms may be absent in some resistant isolates, we aimed at decipher the genetic basis of fosfomycin resistance in E. coli. Different groups of isolates were studied: fosfomycin-resistant mutants selected in vitro from E. coli CFT073 (MIC = 1 mg/L) and two groups (wildtype and non-wildtype) of E. coli clinical isolates. Single-nucleotide allelic replacement was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
(78 reference statements)
1
10
0
Order By: Relevance
“…The UhpT transporter, which is encoded by the uhpT gene, mediates the uptake of hexose‐6‐phosphate (Sonna et al ., 1988 ; Cattoir et al ., 2020 ). The synthesis of UhpT transporter is tightly regulated by the products of the uhpABC regulatory genes: a response regulator UhpA, a histidine kinase UhpB and a receptor/transporter protein UhpC (Islandt and Kadner, 1993 ; Schwöppe et al ., 2002 ; Västermark and Saier, 2014 ; Cattoir et al ., 2020 ). The UhpB protein functions as an activator of UhpA, which regulates uhpT transcription (Weston and Kadner, 1988 ; Wright and Kadner, 2001 ).…”
Section: Regulation Of Phosphatases P O Acquisitio...mentioning
confidence: 99%
See 2 more Smart Citations
“…The UhpT transporter, which is encoded by the uhpT gene, mediates the uptake of hexose‐6‐phosphate (Sonna et al ., 1988 ; Cattoir et al ., 2020 ). The synthesis of UhpT transporter is tightly regulated by the products of the uhpABC regulatory genes: a response regulator UhpA, a histidine kinase UhpB and a receptor/transporter protein UhpC (Islandt and Kadner, 1993 ; Schwöppe et al ., 2002 ; Västermark and Saier, 2014 ; Cattoir et al ., 2020 ). The UhpB protein functions as an activator of UhpA, which regulates uhpT transcription (Weston and Kadner, 1988 ; Wright and Kadner, 2001 ).…”
Section: Regulation Of Phosphatases P O Acquisitio...mentioning
confidence: 99%
“…The UhpC protein has a high sequence similarity to the UhpT transporter (Islandt and Kadner, 1993 ) and can serve as a G6P‐specific transporter with a relatively low transport rate compared to UhpT (Västermark and Saier, 2014 ). The UhpC protein functions as a high‐affinity G6P receptor that signals UhpB to undergo autophosphorylation and activate the UhpA regulator in the presence of external G6P (Wright and Kadner, 2001 ; Västermark and Saier, 2014 ; Cattoir et al ., 2020 ). Thus, the expression of the UhpT transporter is induced by extracellular G6P (Dietz and Heppel, 1971 ; Hoffer et al ., 2001b; Castañeda‐García et al ., 2013 , Cattoir et al ., 2020 ).…”
Section: Regulation Of Phosphatases P O Acquisitio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Porins also mediate transport of other antibiotics across the outer membrane, increasing the risk of multidrug resistance ( 55 ). Indeed, OmpF mutants are resistant to multiple antibiotics ( 56 ), and a galU deletion and point mutant had a 2-fold increase in MIC to fosfomycin ( 57 ). One study found that 42.9% of clinically ceftriaxone-resistant uropathogenic E. coli (UPEC) isolates were multidrug resistant.…”
Section: Discussionmentioning
confidence: 99%
“…19 Fosfomycin resistance is rare in areas with limited use but is on the rise in countries with higher usage, although the susceptibility rates are variable and do not exceed 10% of the isolates. [20][21][22] However, the use of a single dose is associated with a higher percentage of relapses, mainly in patients with recurrent LUTIs. 23 A single dose of fosfomycin-tromethamine and short-courses of nitrofurantoin and pivmecillinam are now recommended by the latest guideline of the European Association of Urology for empirical therapy of uncomplicated LUTI, 24 but no study has compared more than two short-course antimicrobial agents for uncomplicated LUTIs.…”
Section: Introductionmentioning
confidence: 99%